Mathematical SEIR Model of the Lumpy Skin Disease Using Caputo-Fabrizio Fractional-Order (European Journal of Pure and Applied Mathematics, 2025)
Of the seventeen sustainable development goals given out by the United Nations, the third focuses on good health and well-being, while the 15th focuses on life on land. This research aims to study an integral model of Lumpy Skin Disease to establish better knowledge of this condition. In this study, we use the new Caputo-Fabrizio fractional derivative to analyze the Lumpy Skin Disease model. The Picard-Lindelof method serves as a foundation for verifying that the model solutions are both unique and exist. Researchers derive approximate solutions of the Caputo-Fabrizio fractional-order model through a numerical approach which applies fundamental theorem of fractional calculus to the derivative and uses Lagrange polynomial interpolation. The novel approach allows thorough investigation of disease evolution dynamics to generate vital knowledge about disease patterns and control methods. The approach uncovers fresh analytical insights never seen before within the model boundaries. Numerical simulations assess the effects of control parameters on selected compartments from within the model framework. Insights obtained from the graphical results present a detailed view into the model's complexity. Numerical experiments using diverse fractional Caputo-Fabrizio derivatives align with standard integer derivative approaches to show modern fractional derivatives create a clearer account of infectious disease progression. Fractional analysis proves the superiority of using non-integer order derivatives in constructing accurate models for monitoring Lumpy Skin Disease progression.